Development of a 3-component strain-gauge for use on the whirling arm - Holloway, W. G.; Kumar, P. E.; Osbourn, W. (College of Aeronautics, 1969)
This note covers the development of two strain-gauge balances for use on the Whirling Arm Facility of the College. The main requirements for this balance were:- (a) to withstand 700 lbs of sideload without it interfering with the lift, drag and pitching moment measurements, (b) to have a high sensitivity without too heavy a structure. The balance originally designed for this purpose proved to be unacceptable because of undue interference due to sideload and the non-repetitive nature of its calibration curves. With the information gained from this first balance a second balance of exceedingly simpler design, was manufactured and was found to give good calibration curves and sensitivity, with little interference from sideloads. A trouble free method of recording the signals from the strain-gauge bridges is being developed and should be operating within the near future. It concluded that a new model, with its c.g. lying on the transverse centre-line of the balance, will be needed if sideload interference is to be further reduced.